You Never Know What's Going to Happen: Exploring Factors that Influence Older Women's Decisions to Make Arrangements for Future Long-term Care Needs - Cortright, Lindsay M. (East Carolina University, 2016)
While 70% of US elders will require long-term care, few plan accordingly and most decisions are made in a crisis. Data from two-waves of semi-structured interviews with a sample of 10 White and 10 African American, community-dwelling women ages 60-89 in eastern North Carolina are used to examine the relationship between long-term care planning and a range of demographic, social, and attitudinal variables. Ethnicity and experience making long-term residential arrangements for others were significantly associated with planning. Alternatively, having large social support systems inversely impacts planning. Using Grounded Theory to analyze the qualitative data, three clusters of themes showed shared ideas about what it means to grow old and four clusters of themes that may impact women's views on long-term care planning and willingness to plan were differentially shared among the sample. Themes associated with non-planning include the belief that planning for the future is futile, that children will take over their care and decision-making, fear of becoming dependent on loved ones, and aversion to long-term care options that may keep older women from thinking about and talking about their options. Future applications include raising awareness about LTC by distributing information and hosting workshops through local senior centers to encourage conversations and concrete planning for future care needs.
Keywords: seniors; advance care planning; qualitative research; Older women--Care--Planning; Long-term care of the sick--Planning; Grounded theory